2007
DOI: 10.1016/j.eurpsy.2007.01.1051
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of malondialdehyde formation in healthy subjects

Abstract: This result was found for startle probes presented at 2.5s, but not at longer intervals. Conclusions: The MN system is involved in emotional processing, as shown by modulation of the startle reflex when a negative picture is primed with emotionally congruent biological motion. Further, this modulation occurs only when the time interval between picture presentation and startle probe is relatively short, suggesting that the MN system may provide an early warning of threat-related actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…MDA is a biological marker of oxidative stress, which also has a circadian rhythm of formation with the higher levels at noon than 2 p.m. [26]. Our study found that subjects with poor sleep quality had greater MDA levels than good sleep quality groups.…”
Section: Discussionmentioning
confidence: 44%
“…MDA is a biological marker of oxidative stress, which also has a circadian rhythm of formation with the higher levels at noon than 2 p.m. [26]. Our study found that subjects with poor sleep quality had greater MDA levels than good sleep quality groups.…”
Section: Discussionmentioning
confidence: 44%